Perovskite Solar Cells: Stable under Space Conditions. Issue 12 (7th October 2020) - Pérez-del-Rey, Daniel; Dreessen, Chris; Igual-Muñoz, Ana M.; van den Hengel, Lennart; Gélvez-Rueda, María C.; Savenije, Tom J.; Grozema, Ferdinand C.; Zimmermann, Claus; Bolink, Henk J.
Abstract : Metal halide perovskite solar cells (PSCs) are of interest for high altitude and space applications due to their lightweight and versatile form factor. However, their resilience toward the particle spectrum encountered in space is still of concern. For space cells, the effect of these particles is condensed into an equivalent 1 MeV electron fluence. The effect of high doses of 1 MeV e‐beam radiation up to an accumulated fluence to 10 16  e −  cm −2 on methylammonium lead iodide perovskite thin films and solar cells is probed. By using substrate and encapsulation materials that are stable under the high energy e‐beam radiation, its net effect on the perovskite film and solar cells can be studied. The quartz substrate‐based PSCs are stable under the high doses of 1 MeV e‐beam irradiation. Time‐resolved microwave conductivity analysis on pristine and irradiated films indicates that there is a small reduction in the charge carrier diffusion length upon irradiation. Nevertheless, this diffusion length remains larger than the perovskite film thickness used in the solar cells, even for the highest accumulated fluence of 10 16  e −  cm −2 . This demonstrates that PSCs are promising candidates for space applications. Abstract : Quartz‐based perovskite solar cells maintain 19% power conversion efficiency after irradiation with high doses of 1 MeV electrons. Time‐resolved microwave conductivity measurements reveal only a marginal reduction in charge carrier diffusion length after high doses of high energy electron irradiation.